A qualitative exploration of the views of people with lived experience of suicide within the criminal justice system - Walker, T (The journal of forensic psychiatry & psychology, 2022)
Background: Little evidence exists on how individuals in the criminal justice system (CJS) can discuss their experience of self-harm, suicidal ideation and behaviors. They are a valuable resource for suicide prevention in the CJS worldwide. Aims: To explore the views of those with lived experience on what the CJS can do to help support and improve services for those at risk of self-harm and suicide across the criminal justice pathway. Method: Five focus group discussions with 21 experts by experience were analyzed using thematic analysis. Results: The qualitative analysis identified three themes relevant to the process of assessment and prevention of suicide and self-harm risk: knowing my history, being treated as an individual and being able to express vulnerability. Limitations: The focus group design may have made the participants more reluctant to share experiences representing alternative perspectives or personally sensitive information. Conclusion: The findings of this study suggest the CJS needs improved connections across teams to promote continuity of care and the quality of information flow to enable institutions to become more therapeutic. By developing the use of key individual relationships this will ensure that people are treated as individuals, with safe spaces to reveal vulnerabilities.